Two new species of Zodarion Walckenaer, 1826 (Araneae: Zodariidae) from Turkey - Coşar, Ilhan (Zootaxa, 2021)
Two new species of the megadiverse genus Zodarion Walckenaer, 1826, from the Aegean and Southeastern Anatolian regions of Turkey are described and illustrated: Zodarion bozdagensis spec. nov. (♂,♀) from Izmir and Zodarion siirtensis spec. nov. (♂) from Siirt. This contribution increases the total number of Zodarion species to 23 for Turkey. The distribution of these species in Turkey is also mapped.